Discordances between follicle stimulating hormone (FSH) and anti-Müllerian hormone (AMH) in female infertility - Weghofer Andrea; Gleicher Norbert; Barad David H (BMC, 2010)
Abstract Background Follicle stimulating hormone (FSH) and anti-Müllerian hormone (AMH) represent the two most frequently utilized laboratory tests in determining ovarian reserve (OR). This study determined the clinical significance of their concordance and discordance in female infertility patients. Methods We investigated 366 consecutive infertility patients (350 reached IVF), excluding women with polycystic ovarian syndrome (PCOS). They were considered to have normal FSH and AMH if values fell within age-specific (as-) 95% confidence intervals (CI), and to suffer from diminished ovarian reserve (DOR) if FSH exceeded and/or AMH fell below those. The two hormones, thus, could be concordant (Group I), both normal (IA) or abnormal (IB), show normal AMH/abnormal FSH (Group II) or normal FSH/abnormal AMH (Group III). Oocyte yields, stratified for age categories, were then studied in each group as reflection of OR. Results Oocyte yields significantly decreased from groups IA to II to III and IB. Predictive values of as-FSH/AMH patterns changed, however, at different ages. Except at very young and very old ages, normal as-AMH better predicted higher oocytes yields than normal as-FSH, though above age 42 years normal as-FSH predicts good oocyte yields even with abnormally low AMH. Under age 42 discrepancies between as- FSH and as-AMH remain similarly predictive of oocyte yields at all ages. Discussion Concordances and discordances between as-FSH and as-AMH improve OR assessments and predictability of oocyte yields in IVF.